Rol del trabajador social en el desarrollo de una cultura organizacional en el área de operaciones mina cantera, en minera chinalco peru s.a. - 2015. - Medina Rojas, Maria Isabel (2015)
The following research was descriptive and aimed to explain the influence that plays the role of a Social Worker in the develop of an organizational culture in the Operations Mine Area at Minera Chinalco Perú Company, for this study, surveys werw applied related to the roles played by the Social Worker and the level of satisfaction that this has generated in the employees, also the interview and testimony from employees were used, which gave the support and endorsement for what was obtained in the surveys. Surveys has been designed as open questions in order to relate, what was intended to identify and/or recognize to substantiate the progress and development of the organizational culture and the role played bye the social worker. For a better understanding of the subject the report includes chapters that will take an appropriate order of the topics and developed content. In Chapter I, we present the theoretical framework, in which considered the contribution of different authors on the subject, providing the necessary support to their understanding. In this chapter the background of similar studies, theoretical basis and conceptual and operational definitions of our variables are described. In Chapter II , the PROBLEM , which includes the planning and formulation of the problem, hypothesis and objectives are developed . The methodology is also presented in this paper including the variables, type and design of research, population and sample, instruments used and the procedure followed in the preparation of this study. CHAPTER III In the description of the results is done through the presentation of statistical tables and graphs that allow better exposure of the data found; Discussion of results , where we proceeded to compare them with the evidence presented and the different theories raised , allowing to prove the existence of a relationship between variables under study. The conclusions and recommendations that came finished the process of collecting and processing data that allowed the execution of the methodological investigation are presented. Keywords: effective communication, teamwork, conflict resolution, interpersonal relation, organizacional culture.